Blød modernisme: En overset emotionel strømning i efterkrigstidens design - Laura, Heidi (K&K - Kultur og Klasse, 2021)
A significant body of mid-century design has remained relatively unstudied and underrepresented in museum collections due to its figurative and emotional decorations. These designs clashed with the reigning conception of modern style as rational, honest, streamlined and masculine, yet also represent a clearly modern approach to decoration, designed to complement the modern home. A range of mainly Scandinavian designs and designers are discussed in the article. Long neglected for their alleged aesthetic audacity, these works offer insight into the hunger for soothing emotional objects in the post-war era and may best be decoded as “cute” objects provoking ambivalent responses.